Perspectives on Free Speech in China: Editor’s Note - Editor, CJAL (Columbia Journal of Asian Law, 1990)
While some degree of freedom of speech may exist without a formal democratic system, true democracy cannot exist without genuine freedom of speech. For the last half century, the Chinese people have struggled continuously for the right to free speech, many paying the price of imprison- ment or death. In our effort to publish diverse perspectives on Chinese legal reform, the Journal of Chinese Law presents the following two perspectives, which examine the history of the struggle for free speech in China and explore the right to free speech itself. Big Character Posters in China: A Historical Survey examines the history of big character posters (dazibao) in the People’s Republic of China during the last fifty years. Dazibao have become an important political phenomenon in modem China because of their role as a powerful vehicle for expressing political opinion. Written by a Chinese legal scholar, this article provides a unique perspective on many key events in China’s contemporary legal and political history. Between Theory and Practice: The Possibility of a Right to Free Speech in China sets freedom of speech and the respect for individual rights in a theoretical context. Writ- ten as a student note, this essay explores both the basis and the necessity for the right to free speech in China.